Value Relevance of Accounting Information from PSAK 72 - Natatsa Rizqina Mubarika; Rr. Sri Handayani (Jurnal Akuntansi dan Keuangan, 2022)
This study examines the value relevance of accounting information after PSAK 72 on the companies that are listed on Indonesia Stock Exchange. Ohlson’s model is used to evaluate the research hypothesis and to estimate the research model using Generalized Least Squares (GLS) regression analysis. The results indicate that applying PSAK 72 has value relevance to accounting information. Stock price significantly correlates with the company’s earnings, but the book value of equity has no value. PSAK 72 requires professional interpretation and judgment, which resulted in the recognition of differences for similar transactions. The complexity of PSAK 72 requires adjustments for the company to reduce profits, and it will react negatively to the users. PSAK 72 will better disclose its contract revenue with customers, but it requires lengthy preparation. To provide better information, IAI (Ikatan Akuntan Indonesia) needs to consider the transition period for the implementation.